Strategies in technology-enhanced language learning - Zhou, Yalun; Wei, Michael (Studies in Second Language Learning and Teaching, 2018)
The predominant context for strategy research over the last three decades has focused on language learning situated in a conventional classroom environment. Computer technology has brought about many changes in language learning and has become ecological and normalized rather than a supporting tool in the language classroom. Consequently, the landscape of language learning has been rapidly and largely changed with the normalization of technologies in people’s daily communication. The pervasive use of mobile technologies and easy access to online resources require that digital language learners understand and employ appropriate learning strategies for learning effectiveness and that their teachers are able and willing to teach these strategies as needed. This article provides an overview of the state-of-the-art research into technology-enhanced language learning strategies. The strategies under review include those for language learning skill areas, language subsystems, and self-regulated learning. At the end, we discuss the pressing issues that Digital Age language learning has posed to learners, teachers, and researchers and propose considerations for strategy research in digital realms.